2012
DOI: 10.1186/1556-276x-7-431
|View full text |Cite
|
Sign up to set email alerts
|

High-performance III-V MOSFET with nano-stacked high-k gate dielectric and 3D fin-shaped structure

Abstract: A three-dimensional (3D) fin-shaped field-effect transistor structure based on III-V metal-oxide-semiconductor field-effect transistor (MOSFET) fabrication has been demonstrated using a submicron GaAs fin as the high-mobility channel. The fin-shaped channel has a thickness-to-width ratio (TFin/WFin) equal to 1. The nano-stacked high-k Al2O3 dielectric was adopted as a gate insulator in forming a metal-oxide-semiconductor structure to suppress gate leakage. The 3D III-V MOSFET exhibits outstanding gate controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 20 publications
(25 reference statements)
0
16
0
Order By: Relevance
“…Several reports describe use of multiple anodisation steps, with removal of alumina between each step, as a means of improving the uniformity of the porous structure. 34,35 Following this strategy a three-step anodisation protocol was optimised. Two relatively long anodisations were used to improve the uniformity of the dimpled template, whereas the third anodisation was very brief to ensure formation of a shallow membrane.…”
Section: Preparation Of Paa Membranesmentioning
confidence: 99%
“…Several reports describe use of multiple anodisation steps, with removal of alumina between each step, as a means of improving the uniformity of the porous structure. 34,35 Following this strategy a three-step anodisation protocol was optimised. Two relatively long anodisations were used to improve the uniformity of the dimpled template, whereas the third anodisation was very brief to ensure formation of a shallow membrane.…”
Section: Preparation Of Paa Membranesmentioning
confidence: 99%
“…As a solution, an increased dielectric material (high-k) is employed to substitute silicon dioxide (SiO 2 ) in which a thicker dielectric layer can be growth on the top of silicon body without having electrical thickness penalties [5]. The high-k dielectric is normally incorporated with metal-gate for solving the compatibility issue between poly-gate and high-k dielectric that might result in lower on-current (I ON ) [6].…”
Section: Introductionmentioning
confidence: 99%
“…1 Recent studies on III-V FETs have shown fascinating characteristics from thin-channel planner MOSFETs. 2,3 III-V junctionless FET devices have also been reported for even superior on-/off-state current ratio. 4,5 InGaAs/InAlAs is one of highly attractive III-V materials due to little lattice mismatch 6 and outstanding heterojunction transport property.…”
Section: Introductionmentioning
confidence: 99%